INCREASING STUDENTS’ VOCABULARY MASTERY THROUGH PICTURE OF VII GRADE AT SMP NEGERI 4 TOLITOLI - Aprilieah, Reza (Universitas Madako Tolitoli, 2017)
This research aims to solve the problems encountered by students of SMP Negeri 4 Tolitoli in learning English vocabulary. Secondly to describe the procedure in teaching and learning English vocabulary by applying pictures. And thirdly, to find out the result and improvement of the students in teaching English vocabulary in applying pictures. This is pre experimental study used 19 students as a sample. They were seventh grade students of SMP Negeri 4 Tolitoli. Data were taken from pretest and posttest.The data collected show that the mean score 52.05 pretest and 81.00 in posttest. The data of this research were analyzed by SPSS program. Computation of the data T- count was 8.534 with significant level was 0,000. And to related with probality level was 0,05. As the conclusion from assumption T-count > T-table can be proved. The study indicated there is significant different affect after applying the technique to improving the student vocabulary mastery through pictures in the VIIᴮ grade of SMP Negeri4 Tolitoli. Keywords: Increasing Students Vocabulary Mastery, Using Pictures.